PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN PENDIDIKAN KARAKTER RELIGIUS BERBASIS ASWAJA DI MADRASAH ALIYAH MA’ARIF SUKOREJO - Nirmawati, Alfani Apriliani; Mohtarom, Ali; Ma’ruf, Ahmad; Yusuf, Wiwin Fachrudin (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2023)
The role of Islamic Religious Education teachers in instilling religious character in students at Madrasas which aims to increase the cultivation of religious characters through religious activities at their Madrasas. The purpose of this study was to determine the meaning of ASWAJA-based religious character education, to determine the role of Islamic Religious Education educators in instilling ASWAJA-based religious character education at Madrasah Aliyah Ma'arif Sukorejo and to determine the supporting and inhibiting factors of the role of Islamic Religious Education teachers in instilling ASWAJA-based religious character education at Madrasah Aliyah Ma'arif Sukorejo. In this study, the researcher used a qualitative descriptive approach, in which the descriptive meaning itself is a formulation of the problem that becomes a research guide for exploring or photographing social situations that will be thoroughly, broadly and in-depth examined. Data collection is done through observation, interviews and documentation. Then the data is analyzed with stages of data collection, data reduction, data presentation and conclusions. In order to ensure the validity of the data, triangulation of sources and methods is used. The results of the study show that the teacher seeks to instill Religious Character Education in students by carrying out religious teaching activities every day at Madrasah, the role of the teacher as a facilitator, motivator, and inspirer, evaluator, then the process of cultivating religious character at Madrasa Aliyah Ma'arif Sukorejo has supporting and inhibiting factors that come from the conditions of the students themselves and their environment, including the family environment, community and friendship environment.